Engagement in research: an innovative three-stage review of the benefits for health-care performance - S Hanney; A Boaz; T Jones; B Soper (National Institute for Health Research, 2013)
Background: There is a widely held assumption that research engagement improves health-care performance at various levels, but little direct empirical evidence. Objectives: To conduct a theoretically and empirically grounded synthesis to map and explore plausible mechanisms through which research engagement might improve health services performance. A review of the effects on patients of their health-care practitioner's or institution's participation in clinical trials was published after submission of the proposal for this review. It identified only 13 relevant papers and, overall, suggested that the evidence that research engagement improves health-care performance was less strong than some thought. We aimed to meet the need for a wider review. Methods: An hourglass review was developed, consisting of three stages: (1) a planning and mapping stage; (2) a focused review concentrating on the core question of whether or not research engagement improves health care; and (3) a wider (but less systematic) review of papers identified during the two earlier stages. Studies were included in the focused review if the concept of 'engagement in research' was an input and some measure of 'performance' an output. The search strategy covered the period 1990 to March 2012. MEDLINE, EMBASE, PsycINFO, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science and other relevant databases were searched. A total of 10,239 papers were identified through the database searches, and 159 from other sources. A further relevance and quality check on 473 papers was undertaken, and identified 33 papers for inclusion in the review. A standard meta-analysis was not possible on the heterogeneous mix of papers in the focused review. Therefore an explanatory matrix was developed to help characterise the circumstances in which research engagement might improve health-care performance and the mechanisms that might be at work, identifying two main dimensions along which to categorise the studies: the degree of intentionality and the scope of the impact. Results: Of the 33 papers in the focused review, 28 were positive (of which six were positive/mixed) in relation to the question of whether or not research engagement improves health-care performance. Five papers were negative (of which two were negative/mixed). Seven out of 28 positive papers reported some improvement in health outcomes. For the rest, the improved care took the form of improved processes of care. Nine positive papers were at a clinician level and 19 at an institutional level. The wider review demonstrated, for example, how collaborative and action research can encourage some progress along the pathway from research engagement towards improved health-care performance. There is also evidence that organisations in which the research function is fully integrated into the organisational structure out-perform other organisations that pay less formal heed to research and its outputs. The focused and wider reviews identified the diversity in the mechanisms through which research engagement might improve health care: there are many circumstances and mechanisms at work, more than one mechanism is often operative, and the evidence available for each one is limited. Limitations: To address the complexities of this evidence synthesis of research we needed to spend significant time mapping the literature, and narrowed the research question to make it feasible. We excluded many potentially relevant papers (though we partially addressed this by conducting a wider additional synthesis). Studies assessing the impact made on clinician behaviour by small, locally conducted pieces of research could be difficult to interpret without full knowledge of the context. Conclusions: Drawing on the focused and wider reviews, it is suggested that when clinicians and health-care organisations engage in research there is the likelihood of a positive impact on health-care performance. Organisations that have deliberately integrated the research function into organisational structures demonstrate how research engagement can, among other factors, contribute to improved health-care performance. Further explorations are required of research networks and schemes to promote the engagement of clinicians and managers in research. Detailed observational research focusing on research engagement within organisations would build up an understanding of mechanisms. Study registration: PROSPERO: CRD42012001990. Funding: The National Institute for Health Research Health Services and Delivery Research programme.